Analisis Pengaruh Produk Domestik Regional Bruto (PDRB), Upah Minimum Regional (UMR) dan Tingkat Pengangguran Terbuka (TPT) Terhadap Kesejahteraan Dalam Perspektif Ekonomi Islam di Provinsi Sumatera Utara - Siregar, Tarmiji Hamid; Lubis, Fauzi Arif; Inayah, Nurul (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine the influence of PDRB, UMR and TPT on people's welfare (HDI) in North Sumatra Province for the 2017-2021 period. This research is a type of quantitative research that is associative in nature with a sample of 135 data from 27 districts/cities in North Sumatra Province which were collected through documentation from BPS. Data analysis technique using multiple linear regression analysis. The results of the study show: (1) PDRB partially has a positive and significant effect on people's welfare; (2) Partial UMR has no significant effect on the welfare of the community; (3) TPT partially has a positive and significant effect on people's welfare; and (4) PDRB, UMR and TPT jointly (simultaneously) have a significant effect on people's welfare in North Sumatra Province during the 2017-2021 period. The magnitude of the influence of the PDRB, UMR and TPT variables simultaneously on community welfare is 17.6% and the remaining 82.4% is explained by other variables besides the variables proposed in this study.